PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI PADA UPK PUSKESMAS ALIANYANG PONTIANAK - Satriyana Satriyana; Maria Ulfah; Warneri Warneri (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the effect of workload and compensation toward UPKAlianyang Pontianak public health center employee job satisfaction, either insimultaneously as well as partially. The research method which used is descriptiveresearch by means of relationship studies form. The data source in this study isAlianyang Pontianak public health center employee of which the sample is 31people. The sampling taking technique used the cencus sampling technique. And it’sdata used a questionnaire that has been validity and reability testing. The dataanalysis technique which is used to answer hypothesis that multiple regressionanalysis, t test, f test, coefficient of determination (R2). The results of analysis datashow that : (1) workload take positive effect and significant to job satisfaction by tcount of 2.321 and a significant value amounting to 0.028; (2) compensation takepositive effect to job satisfaction 2.717 and a significant value amounting to 0,011;(3) workload and compensation in together way take positive effect and significantto job satisfaction by t value amounting to 7.205 and significance to 0.003. Thecoefficient of determination r2 amounting to 0.340 and can be interpreted that 34%job satisfaction be affected by workload dan compesation while the residual is 66%be affected by other variable outside of this research.Keywords : workload, compensation, and job satisfaction